Spatial and Sectoral Characteristics of Relational Capital in Innovation Activity - Roberta Capello (European Regional Science Association (ERSA), 2001)
The paper presents prima facie evidence of the role of relational capital in innovation activities, and underlines the spatial and sectoral difference of the effects of relational capital on innovation processes. Relational cpaital is defined in this paper as the intensity of information and knowledge exchange measured through the intensity of cooperation among local actors. The paper is structured in two parts. In the first part, a review on the literature is presented, and the similarities and differences between the concept of relational capital and the more common knowledge spillovers is underlined. In the second part, the empirical results of the analysis is presented; the empirical analysis is based on a database built at the firm level, located both in urban and non-urban areas. The database consists of 89 observations, developed in three urban areas (La Spezia, Genova and Savona) and three specialised areas in Liguria, an Italian region. With a quantitative approach, the paper replies to the following key questions: - is relational capital a determinant for innovation activities? - If it is so, does it have the same role in urban and non urban areas? - Does it have a different role in specialised and despecialised areas? The empirical results to these questions help in understanding whether it is true that competitive city regions in the global economy are the major locations for relatively exclusive knowledge and learning resources. Our impression is that it is difficult to support this argument in general: if relational capital plays a role in innovation activities, it may very well be that its role strongly depends on the sectoral as well as the spatial characteristics in which the innovation process takes place. Non-urban areas characterised by strong local synergies and highly specialised activities may even be more facilitated in their inovation activity.
Keywords: 330